2018
DOI: 10.1111/clr.13337
|View full text |Cite
|
Sign up to set email alerts
|

The clinical performance of all‐ceramic implant‐supported single crowns: A systematic review and meta‐analysis

Abstract: Objective This review aimed at evaluating the survival and technical complication rates of all‐ceramic implant‐supported single crowns (SC). Material and Methods Three electronic databases were searched for clinical studies conducted at ≥ 15 patients examining implant‐supported all‐ceramic SCs over ≥ 12 months. Survival rates of implants and restorations plus technical complication rates of SCs were calculated and tested for statistical correlation with confounding variables. Statistical analysis was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
109
3
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(138 citation statements)
references
References 85 publications
8
109
3
14
Order By: Relevance
“…In the present investigation, the KM estimate for chipping events was 48.4% after 5 years. As a result, the chipping frequency in the present study was significantly higher than the estimate calculated by Rabel and collaborates (Rabel et al, ). One reason for this might be considered the fact that reconstructions of the present evaluation were located in posterior regions, whereas multiple investigations in the meta‐analyses included a mixture of both anterior and posterior reconstructions (Chappuis et al, ; Nejatidanesh, Moradpoor, & Savabi, ; Paolantoni, Marenzi, Blasi, Mignogna, & Sammartino, ; Tartaglia, Sidoti, & Sforza, ; Wittneben et al, ; Worni, Kolgeci, Rentsch‐Kollar, Katsoulis, & Mericske‐Stern, ).…”
Section: Discussioncontrasting
confidence: 78%
See 4 more Smart Citations
“…In the present investigation, the KM estimate for chipping events was 48.4% after 5 years. As a result, the chipping frequency in the present study was significantly higher than the estimate calculated by Rabel and collaborates (Rabel et al, ). One reason for this might be considered the fact that reconstructions of the present evaluation were located in posterior regions, whereas multiple investigations in the meta‐analyses included a mixture of both anterior and posterior reconstructions (Chappuis et al, ; Nejatidanesh, Moradpoor, & Savabi, ; Paolantoni, Marenzi, Blasi, Mignogna, & Sammartino, ; Tartaglia, Sidoti, & Sforza, ; Wittneben et al, ; Worni, Kolgeci, Rentsch‐Kollar, Katsoulis, & Mericske‐Stern, ).…”
Section: Discussioncontrasting
confidence: 78%
“…A recent systematic review and meta‐analysis screening the nowadays available literature on implant‐supported all‐ceramic single crowns showed that veneered zirconia‐based reconstructions can still be considered the biggest stakeholder for all‐ceramic implant‐supported replacement of single missing teeth (Rabel, Spies, Pieralli, Vach, & Kohal, ). After 5 years of observation, the meta‐analysis revealed a survival estimate of 92.0% for zirconia‐based bi‐layers, ranging from 67.4% (Bömicke, Gabbert, Koob, Krisam, & Rammelsberg, ) to 100% (Hosseini, Worsaae, Schiodt, & Gotfredsen, ; Lops, Bressan, Chiapasco, Rossi, & Romeo, ; Wittneben et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations